Analisis Peranan Media Sosial Dalam Perilaku Konsumtif di Kalangan Mahasiswa FIS UINSU - Kartini; Asdi, Rahma Sariva; Lubis, Nurmala; Soraya, Eva; Fahri, Zakdi (Ikatan Da'i Indonesia, 2023)
This study aims to find out how consumptive behavior is in shopping on social media among students of FIS UINSU. This study uses a research approach used in this study is a qualitative approach. As for what is meant by qualitative research, namely research that intends to understand the phenomena of what is experienced by research subjects holistically, and by means of descriptions in the form of words and language, in a special natural context and by utilizing various scientific methods (Moleong, 2007:6). The type of this research approach is descriptive. Descriptive research is research that seeks to describe current problem solving based on data. The type of qualitative descriptive research used in this study is intended to obtain information about consumptive behavior in online shopping among students. This study resulted that from the three selected informants, the existing consumptive behavior started from habits and a sense of inclination to continue shopping online on various online shopping platforms. From the three informants, it can be seen that there are informants who like to shop at Shopee, olshop accounts on social media, and even shop at the busy TikTok Shop.